Hubungan Jarak Kelahiran dengan Kejadian Perdarahan Post Partum Primer di PMB A Kec. Bojongloa Kaler Kota Bandung - Lulu Mamlukah Rosmayanti; Windi Tifani; Moch Abimanda Ferdiansyah (NHM PRESS, 2023)
Background: Based on WHO research worldwide, there are 500,000 maternal deaths per year. Postpartum hemorrhage is one of the causes of maternal death. The incidence of postpartum hemorrhage is around 10% and its a direct cause of maternal death. The ideal interval for pregnancy (after a prior pregnancy) is not less than 2 years and not more than 5 years. If the interval is less than 2 years and more than 5 years, it can result in greater maternal mortality which begins with various complications, including postpartum hemorrhage. Methodology: This study uses an analytical approach with a cross sectional design. The sample in this study was 84 samples. Data retrieval using medical record data. The analysis was carried out by univariate and bivariate using the Chi-Square test. Conclusion: There is a relationship between postpartum hemorrhage and inter- pregnancy interval. Keywords: Inter-pregnancy interval, Bleeding, Postpartum